PUNISHABLE ACTS (CRIMINAL ACTS, COMMERCIAL OFFENSES AND MISDEMEANORS) IN THE FIELD OF MINING AND GEOLOGICAL EXPLORATIONS - Milić, Ivan; Drakić, dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The field of mining and geological exploration is exceptionally complex. It is regulated by numerous regulations of varying legal force. In the Republic of Serbia, one principal law governs this field, along with more than twenty by-laws. The principal law in this area, the Law on Mining and Geological Explorations, prescribes criminal acts, commercial offenses, and misdemeanors. One by-law adopted in accordance with the aforementioned law prescribes commercial offenses and misdemeanors. The subject of this paper, as indicated by the title itself, are punishable acts prescribed in this particularly complex field. The aim of the paper is to examine these punishable acts and provide a critical analysis thereof. The authors also present certain proposals for the amendment of existing regulations.